A Learning Community Approach for Post-Secondary Large Lecture Courses - Ehrlick, Steven P.; Slotta, James (Frontiers in Education, 2018)
This design-based research study examined the ways in which a learning community approach can be enacted in large undergraduate lecture courses through a scaffolded, complex curricular design that utilizes active and inquiry-based learning. By combining a traditional lecture with breakout tutorials, the study involved two iterations, firstly by adopting the Fostering Communities of Learners pedagogical model, then by augmenting the model by blending its methodology with elements from a more recent model called Knowledge Community and Inquiry (KCI). Both iterations were evaluated for adherence to, and enactment of, the Fostering Communities of Learners principles. The second iteration was further evaluated to determine the impact of adding a KCI collective knowledge base. Measures included the enactment of the curricular design, achievement of course learning outcomes, the group inquiry project, tutorial activities, pre- and post-term surveys and focus groups for teaching assistants and students. Findings provided evidence of the viability and effectiveness of a learning community approach in large lecture courses at the undergraduate level when combining the learning principles of the Fostering Communities of Learners model with the student-populated dynamic knowledge base. Students achieved both individual and group success in meeting learning outcomes through individual inquiry and collaborative, active learning, with the knowledge base providing a forum for students to share their research and access ideas for their inquiry.